2020
DOI: 10.3390/fib8060036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Milled Glass Fiber Fillers on Mode I & Mode II Interlaminar Fracture Toughness of Epoxy Resin for Fabrication of Glass/Epoxy Composites

Abstract: The present work is focused on improving mode I and mode II delamination resistance of glass/epoxy composite laminates (50 wt.% of glass fibers) with milled glass fibers, added in various amounts (2.5, 5, 7.5 and 10% of the epoxy weight). Including fillers in the interlayer enhances the delamination resistance by providing a bridging effect, therefore demanding additional energy to initiate the crack in the interlaminar domain, which results in turn in enhanced fracture toughness. The maximal increase of mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…However, as the glass powder content increase, the surface color of the filament gets faded, and the texture becomes rough. Previous studies have reported similar effects of glass powder dispersion on the filament surface [31][32][33]. As the melting temperature of glass powder is higher than rPP, the glass powder mixture does not blend perfectly when the melt blending process with rPP results in a rough filament surface [17,27].…”
Section: Filament Fabrication Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…However, as the glass powder content increase, the surface color of the filament gets faded, and the texture becomes rough. Previous studies have reported similar effects of glass powder dispersion on the filament surface [31][32][33]. As the melting temperature of glass powder is higher than rPP, the glass powder mixture does not blend perfectly when the melt blending process with rPP results in a rough filament surface [17,27].…”
Section: Filament Fabrication Analysismentioning
confidence: 69%
“…The new peak at sample rPP + 10% describes the typical spectrum possessed by sodium silicate, which is the constituent of GP material, and it is concluded that the addition of glass powder material to rPP material has been successfully carried out. The addition of glass powder material did not cause a shift in the typical polypropylene peak, but gave rise to a new characteristic peak [ 32 , 39 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sharp peak at 1508 cm −1 and 1605 cm −1 corresponds to the C–C and C=C of aromatic rings. 33,34 The prominent peak in MWCNT/ZrO 2 hybrid nanofiller spectra at 474 cm −1 corresponds to the C–H bending vibration. The weak peaks at 1710 cm −1 and 2353 cm −1 in the MWCNT/ZrO 2 hybrid nanofiller spectrum are attributed to the C=O stretching vibration and bending modes of the –OH group, respectively, originating during synthesis of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The sharp peak at 1508 cm À1 and 1605 cm À1 corresponds to the C-C and C=C of aromatic rings. 33,34 The prominent peak in MWCNT/ZrO…”
Section: Ftir Analysismentioning
confidence: 99%
“…Many factors can cause delamination, e.g., air traps, inadequate resin infusion, or production faults. Delamination lessens the compression strength of wind turbine blades and can induce local buckling in laminated structures [ 30 , 31 , 32 ]. Laminated composites containing delamination can buckle at low compression load levels depending upon the shape and size of delamination.…”
Section: Resultsmentioning
confidence: 99%